Effects of Intrathecal Caffeic Acid Phenethyl Ester and Methylprednisolone on Oxidant/Antioxidant Status in Traumatic Spinal Cord Injuries - Gocmez, Cuneyt; Celik, Feyzi; Kamasak, Kagan; Kaplan, Metin; Uzar, Ertugrul; Arikanoglu, Adalet; Evliyaoglu, Osman (Thieme Medical Publ Inc, 2015)
PurposeTo examine the effect of intrathecally given caffeic acid phenethyl ester (CAPE) on peroxidation and total oxidant and antioxidant systems, and the effect of intrathecally given methylprednisolone (MP) in spinal cord injury (SCI) models. Materials and MethodsFour groups of 10 rats were formed: (1) Laminectomy, intrathecal saline injection, no SCI (sham: S); (2) Laminectomy, intrathecal saline injection, SCI (control: SCI); (3) Laminectomy, intrathecally given single dose of 3 mg/kg MP, SCISCI (SCI+MP). 4) Laminectomy, intrathecally given single dose of 1 mu g/kg CAPE, SCI (SCI+CAPE). Malondialdehyde (MDA), total oxidant activity (TOA), total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione peroxidase (GPx) values in the spinal cord tissue were evaluated. ResultsWhen group S and group SCI were compared, MDA, TOA, and SOD parameters increased post-SCI (p<0.01). When compared with group SCI, it was observed that CAPE and MP decreased the MDA, TOA, and SOD levels (p<0.01). This decrease was more pronounced in the SCI+CAPE group. When group S and group SCI were compared, a statistically substantial decrease was observed in the post-SCI TAC levels. When compared with group SCI, it was shown that CAPE and MP treatment substantially increased TAC levels (p<0.001). ConclusionIntrathecal injection of both CAPE and MP inhibits lipid peroxidation and increase of oxidants in SCIs.
Keywords: spinal cord injury; caffeic acid phenethyl ester; lipid peroxidation; intrathecal